Effectiveness of sorafenib in treating intermediate-stage hepatocellular carcinoma patients refractory to transarterial chemoembolization - Reham Ashour; Eman Rewisha; Mohamed AKL Rady; Sally Waheed Elkhadry; Heba Abdelhalim; Mohamed Atef (BMC Cancer)
Abstract Background Switching to systemic therapy after transarterial chemoembolization (TACE) refractoriness is more inclined to preserve liver function and decrease disease progression. Hence, we conducted a comparison between the advantages of sorafenib therapy and the continuation of TACE in patients with intermediate-stage hepatocellular carcinoma (HCC) who developed TACE refractoriness. Methods This retrospective cohort work involved 1,200 patients with HCC who received TACE therapy at our institution between January 2018 and December 2022. Out of these, a total of 436 participants were determined to be resistant to TACE treatment throughout their clinical progression. Out of them, 271 were finally included and categorized into two groups: (1) patients who shifted from TACE to sorafenib, and (2) patients who maintained TACE treatment. The study assessed the overall survival (OS) and time to disease progression (TTDP) of patients who were resistant to TACE, comparing both groups based on when they achieved Child-Pugh C or acquired advanced-stage HCC. Results Following confirmation of refractoriness to TACE therapy, 163 opted to continue with TACE (TACE group), whereas 108 shifted to sorafenib treatment (sorafenib group). The median TTDP was 23.36 months, while the median OS was 25.3 months, in the sorafenib group, and 11.6 and 14.2 months, correspondingly, in the TACE group (p = 0.0001). Conclusion Switching to sorafenib treatment significantly improved OS and TTDP in patients with intermediate-stage HCC who were refractory to TACE. These finding highlights sorafenib’s potential as an effective alternative for managing disease progression in patients unresponsive to TACE, offering a valuable treatment option in this challenging clinical scenario.